2005
DOI: 10.1093/jjco/hyi071
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of de Gramont's Regimen: Incidence, Clinical Characteristics and Long-term Follow-up

Abstract: de Gramont's regimen has a lower incidence of cardiotoxicity compared with more prolonged 5-FU-based infusion regimens. Nevertheless, patients should still be carefully monitored especially in the first cycles and at night time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 21 publications
0
57
0
2
Order By: Relevance
“…The reported incidence of cardiotoxicity related to 5-FU ranges from 1.2% to 18% [1,2,[12][13][14]. This wide variation is believed to be related to dose dependency as well as the frequency of drug administration.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The reported incidence of cardiotoxicity related to 5-FU ranges from 1.2% to 18% [1,2,[12][13][14]. This wide variation is believed to be related to dose dependency as well as the frequency of drug administration.…”
Section: Epidemiologymentioning
confidence: 99%
“…With shorter bolus regimens, the incidence of cardiotoxicity typically lies between 1.6% to 3% of cases [2]. With more prolonged regimens, these percentages increase to 7.6% to 18% [14]. Recently, a review of 377 cases of 5-FU associated cardiotoxicity confirmed that the majority of cases of cardiotoxicity occur in the setting of continuous infusion [6].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the reversible angina continued up to 12 hours aft er the cessation of 5-FU in 19% of cases and recurred in 90% of patients following readministration 10 . For this reason, it is recommended to stop 5-FU and replace it with another chemotherapeutic agent in case of cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The electrocardiogram (ECG) could showed signs of myocardial ischemia supraventricular tachycardia (SVT) and bradycardia. [7,8] …”
Section: -Flurouracil (5-fu) Is a Chemotherapeutic Drug Which Comesmentioning
confidence: 99%